A BIM-Integrated Stage-Gated Framework for Mitigating Strategic Design Errors in Infrastructure Projects - Alaa T. Alisawi; Ruqayah F. Alrubaye; Philip E. F. Collins (Civil Engineering Journal, 2026)
Design errors remain a persistent challenge in infrastructure delivery, particularly when strategic errors introduced during early design stages propagate into later project phases. This study develops a Building Information Modeling (BIM)-integrated stage-gated framework to mitigate strategic design errors across the infrastructure design lifecycle. The proposed approach embeds interdisciplinary coordination, iterative model federation, and structured verification checkpoints throughout conceptual, preliminary, and detailed design phases. The framework was implemented through a BIM workflow using Civil 3D, Revit, and Navisworks and applied to the Al Najaf Airport Road project in Iraq as a case study. A standards-based geometric and functional assessment was conducted to evaluate both the baseline design and the redesigned solution developed through the proposed framework. The analysis revealed that the baseline design satisfied only 39% of the evaluated design criteria, indicating significant geometric and operational deficiencies. After applying the BIM-integrated framework, the redesigned scheme achieved full compliance with the evaluated standards while eliminating previously undetected coordination conflicts. Model-based analyses also enabled targeted traffic and drainage assessments, helping identify and mitigate potential risks such as flooding susceptibility and unsafe junction configurations prior to construction. The findings demonstrate that early and continuous BIM integration can function as a proactive design assurance and risk management mechanism rather than a late-stage coordination tool. The proposed framework contributes a structured methodology for preventing strategic design errors and improving reliability in BIM-enabled infrastructure projects.